Elongation of protein synthesis: structural basis of the process of decoding - Rodnina, Marina (Henry Stewart Talks, 2007)
Fidelity in biological processes, Elongation step of protein synthesis, Ribosome structures, Ribosomes from different organisms- Errors in protein synthesis, The decoding problem, Kinetic proof-reading, Kinetic model of tRNA selection, Role of induced fit in tRNA selection, Recognition of codon-anticodon complexes by the 30S ribosomal subunit, Local and global conformational changes of the 30S subunit, Interactions of tRNA during decoding, Active role of tRNA, SelB and delivery of Sec-tRNA to the ribosome, Accommodation of tRNA in the A site
Updated at 2018/03/04